Inequality, corruption and the church: challenges and opportunities in the global church - Allaby, Martin (Regnum studies in global Christianity, 2013)
Introduction -- Why extreme inequality and Christianity co-exist -- Thinking about corruption -- Designing the country case studies -- Philippines country case study -- Kenya country case study -- Zambia country case study -- Peru country case study -- Comparisons across the four countries -- Conclusion